Integrating south and southeast Asia through services value chain: The case of India and Thailand - Arpita Mukherjee; Tanu M. Goyal (Indian Council for Research on International Economic Relations (ICRIER), 2015)
Liberalisation and technological developments have led to the fragmentation of production and the emergence of the concept of global value chains. This has ushered in the role of services for linking the production network, resulting in a greater composition of services in the value of tradable. Consequently, liberalisation of the entire value chain is being addressed through trade agreements for efficient cross-country delivery of goods and services. This has also been the case with South and Southeast Asian Free Trade Agreements. The objective of this paper is to understand the prospects of enhancing services trade, investment and cooperation between South and Southeast Asia, taking the example of India and Thailand, by focusing on the development of services value chains through services sector liberalisation. Based on a primary survey and an analysis of the trade agreements involving India and Thailand, the paper finds that the present level of physical and people-to-people integration is low. This is due to the presence of certain market access barriers and regulatory bottlenecks in the two markets. The evidence suggests that these barriers can be addressed at the institutional level by means of a comprehensive trade agreement. India and Thailand have singularly liberalised key services sectors in their concluded bilateral and regional trade agreements, thereby fostering greater integration and leveraging the development of a global value chain.
Keywords: F13; F15; E61; L80; O24; 330; South Asia; Southeast Asia; Market Integration; Value Chain; India; Thailand; Services